Quality and agronomic biofortification of onion as a function of fertilization with micronutrients - Ferreira Bertino, Nubia Marisa (2022)
Fertilization with micronutrients in onion is important to increase the quality of the bulb and its agronomic biofortification will contribute to a greater intake of these nutrients in the diet, reducing the risk of malnutrition and diseases in humans. The aim of this study was to evaluate the influence of fertilization with B, Cu and Zn on the quality and agronomic biofortification of onion. The experiments were carried out from June to November 2018 (Experiment 1) and from June to November 2019 (Experiment 2). The experimental randomized complet block design 15 treatments and four replications. The treatments consisted of the doses of B, Cu and Zn isolated and combined. Bulk agronomic quality and biofortification were evaluated. The combined application of B, Cu and Zn, at doses of 2-4-2 kg ha−1, contributed to increase the pungency in experiment 2. Application of 1 kg ha−1 of B contributed to greater bulb firmness in experiment 1. Fertilization with micronutrients did not increase soluble solids, titratable acidity, SS/TA ratio and bulb color. Onion showed a potential for biofortification of B > Cu > Zn.